Shelf life of mangosteen (Garcinia Mangostana L.) fruit as influenced by maturity, treatment duration, and 1-methylcyclopropene - Apolinario, April Love D. (2008)
Four experiments were conducted to evaluate shelf life of mangosteen fruit treated with the competitive ethylene antagonist 1-methycyclopropene (1-NCP). 1-MCP was used at various concentrations (0, 100, 500, 1000, and 1500 nl l-1). And treatment duration (0, 2, 4, and 6 hours) to treat two maturity stages of mangosteen. Light purple with green streaks (M1) and reddish purple (M2) mangosteen fruit exhibited an average shelf life pf about 11 days. The shelf life of fruit treated with 1000 nl l-1 1-MCP for 4 hours was extended by 83% (MI) and 705 (M2) while the number of days to disease occurrence was delayed by 59% (M1) and 45% (M2). The untreated fruit reached peel color index 6 (black) at 7 (M1) and 5 days (M2). This was reached after 10 (M1) and 8 days (M2) in treated fruit. A visual quality rating of 4 was reached later by treated fruit at 8 and 6 days for M1 and M2, respectively. Control and treated fruit reached sepal quality 2 (21 to 30% shriveling) in 12 and 18 days, while pericarp hardening index 3 (16 to 30%hardening) was reached at 10 and 14 days, respectively. The onset of respiratory peak was delayed for 2 (M1) and 4 days (M2). On the other hand, no differences were observed among treatments in terms of organoleptic quality, percentage weight loss and total soluble solids (TSS) up to 20 days after treatment. Weight loss varied from 4.08 to 26.27% while TSS was 19.990 to 21.730 Brix. Since the variation in postharvest responses did not significantly differ using a higher 1-MCP concentration (i.e. 1500 nl l-1) and a longer treatment duration (i.e. 6 hours), it is recommended that 100 nl l-1 1-MCP for 4 hours be the application rate for mangosteen fruit.